Anhydrite binder based on phosphogypsum technology research - Kazhenova Жанаргүл (Рroblems of engineering and professional education, 2023)
Of all the variety of gypsum-containing industrial waste, the greatest interest in construction is represented by phosphogypsum. One of the effective directions for processing phosphogypsum is the preparation of anhydrite binders based on it. This article deals with the development of anhydrite binder technology based on phosphogypsum.